Vibrational mode-specific dynamics of the F- + CH3CH2Cl multi-channel reaction - Tajti Viktor (PHYSICAL CHEMISTRY CHEMICAL PHYSICS, 2022)
We investigate the mode-specific dynamics of the ground-state, C-Cl stretching (v(10)), CH2 wagging (v(7)), sym-CH2 stretching (v(1)), and sym-CH3 stretching (v(3)) excited F- + CH3CH2Cl(v(k) = 0, 1) [k = 10, 7, 1, 3] -> Cl- + CH3CH2F (S(N)2), HF + CH3CHCl-, FHMIDLINE HORIZONTAL ELLIPSISCl- + C2H4, and Cl- + HF + C2H4 (E2) reactions using a full-dimensional high-level analytical global potential energy surface and the quasi-classical trajectory method. Excitation of the C-Cl stretching, CH2 stretching, and CH2/CH3 stretching modes enhances the S(N)2, proton abstraction, and FHMIDLINE HORIZONTAL ELLIPSISCl- and E2 channels, respectively. Anti-E2 dominates over syn-E2 (kinetic anti-E2 preference) and the thermodynamically-favored S(N)2 (wider reactive anti-E2 attack angle range). The direct (a) S(N)2, (b) proton abstraction, (c) FHMIDLINE HORIZONTAL ELLIPSISCl- + C2H4, (d) syn-E2, and (e) anti-E2 channels proceed with (a) back-side/backward, (b) isotropic/forward, (c) side-on/forward, (d) front-side/forward, and (e) back-side/forward attack/scattering, respectively. The HF products are vibrationally cold, especially for proton abstraction, and their rotational excitation increases for proton abstraction, anti-E2, and syn-E2, in order. Product internal-energy and mode-specific vibrational distributions show that CH3CH2F is internally hot with significant C-F stretching and CH2 wagging excitations, whereas C2H4 is colder. One-dimensional Gaussian binning technique is proved to solve the normal mode analysis failure caused by methyl internal rotation.